Lower extremities strength differences in female volleyball players with stage 1 patellar tendinopathy - Kabacinski, J.; Murawa, M.; Fryzowicz, A.; Gorwa, J.; Dworak, L. B. (The Journal of Strength and Conditioning Research, 2022)
The main purpose of the study was to compare the muscle strength between the involved knee (IK) and uninvolved knee (UK) in 12 female volleyball players with stage 1 chronic patellar tendinopathy. Evaluation included the isometric maximal strength to body mass (MS/BM) of the lower extremities extensors for unilateral and bilateral conditions, concentric isokinetic peak torque to body mass (PT/BM) of the hamstrings and quadriceps at 60°·s-1 and 180°·s-1, IK to UK extensors maximal strength ratio (SR), IK to UK hamstrings (or quadriceps) peak torque ratio (TR), and hamstrings to quadriceps peak TR (H/Q). The results indicated a significantly lower unilateral and bilateral MS/BM of lower extremities extensors for IK than UK (p < 0.001). However, there were no significant differences in SR variable between the unilateral condition and bilateral condition (p = 0.448). Only at the 60°·s-1 velocity, significantly lower quadriceps PT/BM for IK compared with the UK (p < 0.001) and the control group (p < 0.001) were observed. Torque ratio related to the quadriceps group was significantly lower at 60°·s-1 than 180°·s-1 (p = 0.004). Furthermore, significantly higher H/Q for IK compared with UK (p < 0.001) and control group (p = 0.008) only at 60°·s-1 was found. These findings show a significant isometric strength asymmetry for both unilateral and bilateral conditions and a significant concentric strength asymmetry at the low velocity. This study suggests strengthening the weaker quadriceps group and balancing the strength between hamstrings and quadriceps within the knee with patellar tendinopathy.